2010
DOI: 10.1159/000312424
|View full text |Cite
|
Sign up to set email alerts
|

Transitional Cell Carcinoma of the Bladder Manifestating as Malignant Lymphoma with Generalized Lymphadenopathy

Abstract: Bladder cancer usually spreads via the lymphatic and hematogenous routes, the most common sites of metastases of urinary bladder cancers being the regional lymph nodes, liver, lung, bone, peritoneum, pleura, kidney, adrenal gland and intestines. Generalized lymph node metastasis of transitional cell cancer of the bladder is extremely rare. According to our literature search, there has been no case report of transitional cell cancer of the bladder that manifests as an extensive large lymph node metastasis invol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
8
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 10 publications
(12 reference statements)
0
8
0
Order By: Relevance
“…5 cinoma for frequency and location of metastasis. Urinary urothelial carcinoma could rarely occur in a lymphomalike pattern with supraclavicular lymph node involvement (22). For supraclavicular metastasis of urothelial cancer, there were no reported cases for curative neck dissection in the literature.…”
Section: Discussionmentioning
confidence: 99%
“…5 cinoma for frequency and location of metastasis. Urinary urothelial carcinoma could rarely occur in a lymphomalike pattern with supraclavicular lymph node involvement (22). For supraclavicular metastasis of urothelial cancer, there were no reported cases for curative neck dissection in the literature.…”
Section: Discussionmentioning
confidence: 99%
“…Kancharla et al . [ 7 ] in 2010 reported the first case of TCC bladder with retroperitoneal and axillary lymphadenopathy where the patient had initially presented with hematuria and was later diagnosed to have disseminated lymphadenopathy. Our case is the first case where an asymptomatic patient presented with upfront massive axillary LN metastasis and retroperitoneal lymphadenopathy detected by 18 F-FDG PET.…”
Section: Discussionmentioning
confidence: 99%
“…A 9-year review of patients with head and neck metastases from 845 urogenital tract tumors (kidney, prostate, bladder, testes, penis, urethra and ureter) showed that only 31 (3.7%) of these tumors developed metastases to the cervical and supraclavicular lymph nodes [6] . There has been one case report of transitional cell cancer of the bladder is mentioned that manifested as an extensive large lymph node metastasis involving the intraparotid, supraclavicular, axillary and regional abdominal and pelvic lymph nodes without bone or visceral organs involved [7] .…”
Section: Discussionmentioning
confidence: 99%